2019
DOI: 10.4103/wjnm.wjnm_66_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of 177Lutetium-prostate-specific membrane antigen therapy in metastatic castration-resistant prostate cancer patients: First experience in West Asia – A prospective study

Abstract: Prostate-specific membrane antigen (PSMA) is a transmembrane protein that is highly expressed on the surface of prostate cancer (PC) cells, making it an excellent radiotracer for both therapeutic and diagnostic purposes. In this prospective study, we investigated the efficacy and toxicity of 177 Lutetium (Lu)-PSMA in metastatic castration-resistant PC (mCRPC) patients for the establishment and approval of this therapy in Iran. Fourteen mCRPC patients (mean age 70.57 ± 7.3 years) were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The salient features of reviewed studies are summarized in Table 1. With regard to predictors of response to therapy and overall survival, numerous studies have shown that patients with PSA decline in response to RLT experience longer overall survival compared to those who do not respond [12,[17][18][19][20][21][22][23][24][25]. It also appears that the degree of PSA decline correlates with the outcome.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The salient features of reviewed studies are summarized in Table 1. With regard to predictors of response to therapy and overall survival, numerous studies have shown that patients with PSA decline in response to RLT experience longer overall survival compared to those who do not respond [12,[17][18][19][20][21][22][23][24][25]. It also appears that the degree of PSA decline correlates with the outcome.…”
Section: Reviewmentioning
confidence: 99%
“…A minority of patients had high-grade hematological toxicities that were dose-dependent. Typically, platelets nadir around four weeks after therapy, while the leukocyte count nadirs around two weeks after therapy [18,25]. Cytopenias are generally transient, with counts eventually returning to normal ranges.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…PSMA-targeted RPT has provided a new alternative to managing patients with advanced PC refractory to other therapies 54 , 55 . Recent prospective trials of 177 Lu-based therapies have demonstrated substantial imaging and PSA responses 56 , 57 . Fewer side effects than other systemic therapies, such as hormonal or chemotherapy, have repeatedly been shown 58 .…”
Section: Discussionmentioning
confidence: 99%
“…PSMA-targeted RPT has provided a new alternative to managing patients with advanced PC refractory to other therapies 54,55 . Recent prospective trials of 177 Lu-based therapies have demonstrated substantial imaging and PSA responses 56,57 . Fewer side effects than other systemic therapies, such as hormonal or chemotherapy, have repeatedly been shown 58 .…”
Section: Discussionmentioning
confidence: 99%